2007
DOI: 10.1080/13548500500429338
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress, psychological stress and allostatic load

Abstract: The mechanism by which chronic caregiving stress results in poor health is not well understood. The objective was to determine whether such a mechanism may be allostatic load, a novel concept specifying physiological systems that may suffer cumulative wear and tear following chronic stress, leading collectively to poor health. The study examines the association of allostatic load with environmental and psychological stress in the contexts of dementia caregiving and relinquishment of care, and is a 2-year longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 40 publications
4
82
2
2
Order By: Relevance
“…Results suggest that consequences to health care due to political conflict are evident in both emergency as well as primary care. Reports by doctors in this study linking the chronic stress of political conflict to diseases like diabetes and heart problems are in line with the increasing amount of knowledge about the effect of chronic stress on health (Clark et al 2007;McEwen 2000). Results also demonstrate the considerable consequences for health care workers in terms of stress.…”
Section: Discussionsupporting
confidence: 57%
“…Results suggest that consequences to health care due to political conflict are evident in both emergency as well as primary care. Reports by doctors in this study linking the chronic stress of political conflict to diseases like diabetes and heart problems are in line with the increasing amount of knowledge about the effect of chronic stress on health (Clark et al 2007;McEwen 2000). Results also demonstrate the considerable consequences for health care workers in terms of stress.…”
Section: Discussionsupporting
confidence: 57%
“…Evidence that stress increases over time for caregivers was found by Clark, Bond and Hecker. 38 In a longitudinal study of new caregivers (M 5.4, SD 3 months of caregiving), veteran caregivers (M 39.7, SD 17.9), and noncaregivers, veteran caregivers reported significantly more perceived stress than did new caregivers. Perceived stress was a predictor of allostatic load (the cumulative toll of the body's attempt to achieve stability through change or allostasis), 39 which increased for both caregiving groups over the study year.…”
Section: Caregiver Stressmentioning
confidence: 98%
“…Few studies have demonstrated an association between stressful life events and a measure of multisystem physiological dysregulation (15)(16)(17)(18)(19). Rather, most have focused on individual biological measures believed to be part of the stress response.…”
Section: Link Between Stressful Life Events and Physiologymentioning
confidence: 99%